2004
DOI: 10.1111/j.1523-1755.2004.00725.x
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone enhances renal calcium reabsorption by two types of channels

Abstract: Aldosterone increases Ca(2+) transport by the distal luminal membranes through L- and T-type Ca(2+) channels, and this action requires tyrosine kinase activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 40 publications
0
11
0
1
Order By: Relevance
“…Surprisingly, CaV3.1 is also found expressed in the distal nephron of the kidney (Andreasen et al 2000), where it may be involved in Ca 2? reabsorption (Leclerc et al 2004). …”
Section: Atp-binding Cassette Transporters: the Abc Of CD 21 Efflux?mentioning
confidence: 97%
“…Surprisingly, CaV3.1 is also found expressed in the distal nephron of the kidney (Andreasen et al 2000), where it may be involved in Ca 2? reabsorption (Leclerc et al 2004). …”
Section: Atp-binding Cassette Transporters: the Abc Of CD 21 Efflux?mentioning
confidence: 97%
“…Although aldosterone is known to enhance Na + reabsorption by the distal nephron, its enhancement of Ca 2+ transport is a relatively new phenomenon. It appears that the effect of aldosterone on increased Ca 2+ transport in the distal luminal membranes is through L‐ and T‐type Ca 2+ channels, which require tyrosine kinase activity 168 . Another hormone that has been shown to enhance transepithelial Ca 2+ transport is arginine vasopressin 5,169 .…”
Section: Endocrine Regulation Of Ca2+ Transportmentioning
confidence: 99%
“…Towards this, we and others have shown that high aldosterone levels are associated with high PTH levels [5][6][7][8][9]. In experimental studies it has been demonstrated that aldosterone excess increases renal and fecal loss of calcium [8][9][10]. This in turn results in secondary hyperparathyroidism which could be effectively treated by mineralocorticoid receptor (MR) blocking therapy in rats [8,9].…”
mentioning
confidence: 93%